Lessons Learned of Zakat Management from Different Era and Countries - Masyita, Dian (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
Zakah and its problems are as old as the Islamic civilization. This Islamic financial instrument is mandatory for Muslims who are capable and expected to reduce the poverty of the people. The potential of zakah in Indonesia reaching 217 trillion rupiah Indonesia's GDP should be able to be explored and distributed to Indonesian Muslims as effectively as possible. Potential only remains just a potential if it is not able to be realized into zakah funds collection that is ready to be distributed to the recipient who is entitled to receive it. The concept of localization/decentralization can be considered as the best way in zakah disbursement. The concept of localization/zoning or decentralization in the distribution of zakah funds closely matches the concept of Sharma in the tax disbursement issue that states that the transfer of power, resources, and responsibilities from the center to the regions is more effective in alleviating poverty in Indonesia.DOI: 10.15408/aiq.v10i2.7237